THE ROLE OF READINESS OF WORK-HOME RESOURCES AND WORK MOTIVATION IN MINIMIZING WORK-FAMILY CONFLICT IN THE COVID-19 PANDEMIC ERA - Amin, Shofia; Raudhoh, Siti (Universitas Brawijaya, Indonesia, 2021)
Physical distancing and stay-at-home instructions to break the chain of the spread of Covid-19 have led various organizations to change their work policy from work from the office to work from home. The specific objective of this study is to examine the link between the readiness of work-home resources in carrying out work from home, work motivation, and work-family conflict. The questionnaire is distributed to lecturers of public higher education institutes in Indonesia through online media by quantitative methods. Data from 131 respondents were then processed using SEM-SmartPLS. The results showed that work-home resource readiness negatively affected work-family conflict and significantly positively affected work motivation. Work motivation has no significant positive impact on work-family conflict. Thus, work motivation cannot mediate the relationship between work-home resource readiness and work-family conflict. Further research regarding work-home resources readiness in another job field would give a different perspective as lecturers have more independent working time than other employees.